Factors Associated with and Temporal Trends in the Use of Radiation Therapy for the Treatment of Pituitary Adenoma in the National Cancer Database - Fathy, Ramie; Kuan, Edward; Lee, John Y. K.; Grady, M Sean; Alonso-Basanta, Michelle; Palmer, James N.; Adappa, Nithin D.; O'Malley, Bert W., Jr.; Brant, Jason (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective Radiation therapy represents an uncommon but important component of treatment plans for some pituitary adenomas (PAs). Although radiation therapy has been used to treat pituitary adenomas for over a century, general trends in the usage of radiation therapy for this purpose have not been reviewed. Additionally, there are few large studies evaluating how radiation therapy is used for the treatment of these benign tumors. Investigating these trends and identifying any variations in radiation therapy utilization would help to better inform treatment decisions and improve patient outcomes.Design Present study is a retrospective analysis of cases using the National Cancer Database.Setting The research was organized at a tertiary academic medical center.Participants Patients were diagnosed with pituitary adenoma between 2004 and 2014 within the National Cancer Database (NCDB).Methods Temporal trends in the usage of radiation therapy to treat pituitary adenoma were analyzed through a retrospective analysis of 77,142 pituitary adenoma cases from the NCDB between 2004 and 2014. Univariate and multivariate analyses were to examine the relationship between patient, tumor, and treatment factors, and the incorporation of radiation therapy into the treatment of pituitary adenomas. We adjusted for potential confounders such as age, sex, race, comorbidity score, facility type, and year of diagnosis.Results A total of 77,142 patients met inclusion criteria. Inclusion of radiation therapy in pituitary adenoma treatment was 8.0% in 2004 and steadily declined to a low of 3.1% in 2014. Overall, patients were less likely to receive radiation for their pituitary adenoma over time (p < 0.001). Similarly, patients were found to be less likely to receive any type of treatment for PA over time (p < 0.001). Multivariable evaluation found patients who were female, between 54 and 64 years of age, or treated at either a Comprehensive Community Cancer Program or an Integrated Network Cancer Program were more likely to receive radiation as part of their pituitary adenoma treatment (p < 0.001, odds ratio [OR] = 2.01, confidence interval [CI]: 1.54–2.63; p < 0.001, OR = 1.84, CI: 1.38–2.44, respectively). Patients were less likely to receive radiation for their PA if they were African American (p < 0.001, OR = 0.81, CI: 0.72–0.91). Logistic regression also identified a progressive increase in the likelihood of receiving radiation after a PA diagnosis with increasing tumor size starting with microscopic tumors, peaking at 4 to 5 cm (p < 0.001; OR = 15.57; CI: 12.20–19.87).Conclusion In this sample of pituitary adenoma patients treated at NCDB institutions between 2004 and 2014, we found a steady decline in the incorporation of radiation therapy in treatment, as well as in the use of any type of intervention for PA treatment, suggesting a rise in noninterventional observation of PA.
Keywords: radiation therapy; pituitary adenoma; national cancer database; temporal trends; radiation; watchful waiting; skull base; anterior skull base